Automated Social Commerce Workflow: Analisis Efektivitas Sistem Shopee Affiliate dalam Mengotomatisasi Promosi, Pengelolaan Link, dan Konversi Penjualan - Ricke Arifa Novitasari; A Sobandi; Abi Sopyan Febrianto (LPPM Universitas Koperasi Indonesia, 2026)
Introduction of social commerce has changed the digital trade system in Indonesia and Shopee Affiliate is one of the platforms that uses automatic workflow to increase the effectiveness in promoting a product. The objective of this study is to determine the extent to which the Shopee Affiliate system can automate these three key components, i.e., product promotion, affiliate link management and sales conversion. Qualitative research with case study design was conducted and the data were gathered through platform observation, interviews with active affiliate marketers, and examination of system documents. It was found from results that the automated process of Shopee Affiliate increases promotional efficiency by using product recommendation engine, easy to track and manage links with the help of integrated dashboard and boost sales conversion compared to manually link promotion. However, some limitations were highlighted including the reliance on platform algorithms and the presence of a learning curve in how to optimize promotional strategies. This study improves our understanding of the impact of automation on social commerce and suggests insights for affiliate marketers to explore how they can better utilize automated workflow systems.